How The West Has Won: Regional and Industrial Inversion in U.S. Patent Activity - Daniel K.N. Johnson; Amy Brown (Wellesley College, Department of Economics, 2002)
While it is clear that there has been a 'regional inversion' in American patent activity over the past 25 years (i.e. relative rise of the Northwest and Southwest at the expense of the traditional invention hotbeds of the Northeast and Midwest), the reason is still open to speculation. Intuition suggests that it can be explained by some combination of changing demographics and industrial composition. We introduce constant market share analysis (CMSA), typically used only in international trade theory, offering a new extension to this tool, and conclude that industrial shifts have accounted for almost half of the regional inversion. Regression results show how the West capitalized upon the shift using demographics and policy variables, whose importance vary with the planning horizon.
Keywords: L0; R11; O38; R15; R12; O30; 330; invention; geography; clustering; regional inversion; constant market share analysis; Patent; Regionale Konzentration; USA